Screens of blood : a critical approach to film and television violence - Desilet, Gregory E. (McFarland & Company, Inc., Publishers, 2014)
"Civilization seems to be moving towards the power of words over weapons. But many still believe wrongs can be righted with violence. The transition to a healthier mythology is seen in an alternative trend in depictions of violence in storytelling. This book examines this trend by comparing examples from film and television with the traditional popular dramatic approach"--